Use of TED Talks video materials in teaching oral liaison interpreting in a non-language university - Maria Valerievna Belorukova; Marina Vianorovna Zolotova (Вестник Майкопского государственного технологического университета, 2023)
The article discusses the use of video materials of public speaking of the TE D Talks platform as a means of teaching liaison interpreting in a non-linguistic university. The key features of TED Talks and the benefits of their use compared with feature films have been formulated. The relevance of using these video materials is determined by their ability to expand the horizons of students through a variety of topics, demonstrate various national versions of the English language and accents, convey the speaker's emotions and introduce the structure of public speech in English. The research problem is to identify the difficulties faced by a student studying oral interpretation, and provide solutions through the use of the specified format of video materials. The purpose of the study is to substantiate the need for the use of TED Talks in teaching liaison interpreting. The main research method is system analysis. The result of the research is the experience of implementing interpretation training with TED Talks on the example of groups with Intermediate proficiency level and higher. Methods of classroom work have been given, graded by complexity and number of participants. Conclusions have been made that the specificity of video recordings of public speeches of TED Talks contributes not only to the successful practice of liaison interpreting, but also to its adequate assessment in a classroom environment.